2021
DOI: 10.1186/s12872-021-02374-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extent of coronary artery disease and percutaneous revascularization assessed by the SYNTAX score on outcomes following transcatheter aortic valve replacement

Abstract: Objectives The aim of the study was to analyze the impact of concomitant coronary artery disease (CAD) assessed by the SYNTAX score (SS) and periprocedural percutaneous coronary intervention (PCI) on outcomes after transcatheter aortic valve replacement (TAVR). Background Due to controversial data regarding the effect of CAD on outcomes after TAVR, proper revascularization strategies remain a matter of debate. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Aortic stenosis (AS) and coronary artery disease (CAD) can be found concomitantly in up to 50% of patients with the former 1,2 and in up to 70% of patients undergoing transcatheter aortic valve implantation (TAVI) 3 . Furthermore, CAD is associated with poorer outcomes in patients undergoing either TAVI 4 or surgical aortic valve replacement (SAVR) 5 …”
Section: Introductionmentioning
confidence: 99%
“…Aortic stenosis (AS) and coronary artery disease (CAD) can be found concomitantly in up to 50% of patients with the former 1,2 and in up to 70% of patients undergoing transcatheter aortic valve implantation (TAVI) 3 . Furthermore, CAD is associated with poorer outcomes in patients undergoing either TAVI 4 or surgical aortic valve replacement (SAVR) 5 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] To date, the benefit of coronary revascularization in the setting of TAVI has been mainly investigated in small, nonrandomized studies, and results are contradictory. 5,6,8,10 The ACTIVATION study is the only randomized clinical trial that explored the benefit of PCI in patients undergoing TAVI with significant CAD. 14 The trial showed similar rates of the primary composite end point of allcause death and rehospitalization at 1 year in patients receiving PCI or not (41.5% versus 44.0%).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Nevertheless, indication for treatment of significant CAD in TAVI setting still remains a matter of debate, due to the marked inconsistency of the available evidence, which are mainly based on nonrandomized data. 2,[5][6][7][8][9][10][11][12] In fact, whether performing PCI and achieving complete revascularization in patients undergoing TAVI would offer a clinical benefit in patients with significant CAD remains unclear. 13 The randomized, noninferiority ACTIVATION trial (Percutaneous Coronary Intervention Prior to Transcatheter Aortic Valve Implantation) showed that rates of death and rehospitalization at 1 year were similar between PCI and no PCI prior to TAVI.…”
mentioning
confidence: 99%
“…The European Society of Cardiology (ESC) guidelines recommend PCI for coronary artery diameter stenosis > 70% in proximal segments (Class of recommendation: IIa; Level of evidence: C) in patients undergoing TAVR with concomitant CAD, with dual antiplatelet therapy (DAPT) recommended after PCI with a duration established according to bleeding risk [2] (Table 1). Prior PCI seems to have a beneficial impact on the long-term prognosis of TAVR patients with concomitant CAD [69], as incomplete revascularization has been associated with a higher rate of mortality [79,[82][83][84]. There is a lack of robust data on the optimal strategy and timing of PCI among TAVR patients with concomitant CAD, since only one underpowered randomized trial evaluated the impact of prior PCI in this population [85].…”
Section: Myocardial Infarction Periprocedural Myocardial Injury and C...mentioning
confidence: 99%